Procesos tributarios y su incidencia en el cumplimiento de las obligaciones tributarias de la Piladora Santa Narcisa - Paredes Chávez, Narcisa Lisbeth (2020)
The present case study consists of analyzing the movements carried out by the company through the analytical method since this method is focused on the decomposition of a whole to determine the nature, cause and effect of a study, the purpose of this method is to delimit the causes that caused its incidence in the fulfillment of the company's tax obligations since it is part of its purpose of the study on the “Santa Narcisa” Stacker, to carry out this entire process the data collection method will be implemented through the interview, The data obtained as a result was the lack of knowledge about tax processes and compliance with tax obligations. Therefore, the following conclusions were generated that the company does not have an accounting system to keep double-entry accounting for costs and expenses, thus not being able to determine costs in the items for the entire period in all products, in their declarations VAT, Income Tax declaration, ATS Annexes, with access to the SRI that was allowed by the owner for the case study, after reviewing each of the obligations of the entire process corresponding to 2018, it was possible to demonstrate that there are indeed several errors in the context of the obligations, such as the statements do not fit, which by consequences led to fines and sanctions, however, it must be clear and emphasize that each company has to issue its accounting policies, standards and procedures especially in the financial area with the sole intention of making all the movements and tax obligations under the knowledge and criteria of professional who is in charge to avoid fines.